Redescription of Chone americana Day, 1973 (Polychaeta: Sabellidae) and description of five new species from the Grand Caribbean Region - Tovar-Hernández, María Ana (Zootaxa, 2005)
In this study Chone americana Day, 1973 from off the coast of North Carolina is redescribed and five new species are described from the Grand Caribbean region, as part of a revision of the genus. Chone americana is easily distinguishable from the other species by the presence of a pygidial cirrus, a radiolar membrane extending beyond half of the branchial crown length and long-sized radiolar tips. The unique distinguishing features for each new species are as follows: Chone diazi sp. nov. has completely exposed branchial lobes beyond the collar segment. In Chone farringtonae sp. nov. the main fang of posterior abdominal uncini extends beyond breast, and posterior peristomial ring collar length is twice as long as chaetiger 1. In Chone johnstonae sp. nov. the middorsal collar margin forms a broad gap. Chone perkinsi sp. nov. has a glandular ridge on chaetiger 2 broadest dorsally. Chone uebelackerae sp. nov. has a triangular pygidium and long radiolar tips. A taxonomic key for Chone species from the Grand Caribbean is included.